The Development of Small and Medium Businesses (MSMEs) Based on Tecnology to Deal with The Industrial Revolution 4.0 - Qotrunnada Ratri Hamidah; Agung Tri Pambudi Sejati; Ana Zulfatu Mujahidah (Universitas Sebelas Maret, 2019)
This article aims to find out the procedures for the development of technology-based Micro, Small and Medium Enterprises (MSMEs) to face the era of the industrial revolution 4.0. The research method used is the study of literature. Data collection is carried out by conducting a study of the review of books, literature, notes, and reports that have to do with the problem being solved. The sources of literature in this study were obtained from books, journals, and research results (papers, theses, and theses) so in this article include general processes which include: systematically identifying theories, finding literature, and analyzing documents that contains information related to the research topic. The results of this study are expected to find ways to develop production results in technology-based Micro Small and Medium Enterprises (MSMEs) to be able to compete in the international class to support Indonesia towards the industrial revolution era 4.0.